Genome-Wide Identification of RNA Editing Sites Affecting Muscle Development in Yak - Wu, Xiaoyun; Chu, Min; Ma, Xiaoming; Pei, Jie; Xiong, Lin; Guo, Xian; Liang, Chunnian; Yan, Ping (Frontiers in Veterinary Science, 2022)
Skeletal muscle growth and development is a complicated process that is regulated at multiple steps and by numerous myogenesis genes. RNA editing represents one of the events at the post-transcriptional level, which contributes to the diversity of transcriptome and proteome by altering the nucleotides of RNAs. However, RNA editing events in the skeletal muscle of yaks are still not well defined. This study conducted whole-genome RNA-editing identification in skeletal muscle of yaks at embryonic stage (ES) and adult stage (AS). We found a total of 13,312 unique RNA editing sites, most of which were detected in the intergenic region. After annotation, we totally identified 3,284 editing sites within coding regions, among which 1,037 were missense changes. Moreover, totally 322 editing sites in the 3’ untranslated regions (UTR) were also predicted to alter the set of miRNA target sites, indicating that RNA editing may be involved in translational repression or mRNA degradation. We found 1,011 RNA editing sites (involving 281 common genes) that are edited differentially in ES as compared to AS. According to the KEGG enrichment analysis, these differentially edited genes were mainly involved in pathways highly related to skeletal muscle development and myogenesis, including MAPK, AMPK, Wnt, and PI3K-Akt signaling pathways. Altogether, our work presents the first characterization of RNA editing sites within yak skeletal muscles on a genome-wide scale and enhances our understanding of the mechanism of skeletal muscle development and myogenesis.